Measurement of habitual physical activity performance in adolescents with cerebral palsy: A systematic review - Clanchy, K.; Tweedy, S.; Boyd, Roslyn (2011)
Aim This systematic review compares the validity, reliability, and clinical use of habitual physical activity (HPA) performance measures in adolescents with cerebral palsy (CP). Method Measures of HPA across Gross Motor Function Classification System (GMFCS) levels I-V for adolescents (10-18y) with CP were included if at least 60% of items reported HPA performance in the domains of intensity, frequency, duration, and mode. Results Seven measures of HPA performance met the criteria: StepWatch, pedometers, Uptimer, heart rate flex method, accelerometers, and self-report measures including the Children's Activity Participation and Enjoyment (CAPE) scale and the Physical Activity Questionnaire for Adolescents. The CAPE scale had the strongest validity and reliability but was limited by its inability to measure activity intensity. No study was identified that evaluated the psychometric properties of physical activity measures in non-ambulant adolescents with CP (GMFCS levels IV and V). Interpretation When deciding on an appropriate measure of HPA in adolescents with CP, clinicians need to consider their research question including the domains of HPA they are evaluating and the population they wish to assess. Accelerometers provide the most robust information about the patterns of HPA, with some evidence of validity but limited data on reliability. Further research is needed to compare the use of tri- and uniaxial accelerometers. © The Authors. Developmental Medicine & Child Neurology © 2011 Mac Keith Press.